Synthesis, Structural Characterization and Catalytic Activity of A Cu(II) Coordination Polymer Constructed from 1,4-Phenylenediacetic Acid and 2,2’-Bipyridine - Wang Li-Hua; Liang Lei; Wang Xin (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
In order to study the catalytic activity of Cu(II) coordination polymer material, a novel 1D chained Cu(II) coordination polymer material, [CuL(bipy)(H2O)5]n (A1) (H2L = 1,4-phenylenediacetic acid, bipy = 2,2’-bipyridine), has been prepared by the reaction of 1,4-phenylenediacetic acid, 2,2’-bipyridine, Cu(CH3COO)2·H2O and NaOH. The composition of A1 was determined by elemental analysis, IR spectra and single crystal X-ray diffraction. The results of characterization show that each Cu(II) atom adopts six-coordination and forms a distorted octahedral configuration. The catalytic activity and reusability of A1 catalyst for A3 coupling reaction of benzaldehyde, piperidine, and phenylacetylene have been investigated. And the results show that the Cu(II) complex catalyst has good catalytic activity with a maximum yield of 54.3% and stability.